A Dostoevskii companion : texts and contexts - Bowers, Katherine; Doak, Connor; Holland, Kate; Dostoyevsky, Fyodor, 1821-1881 (Cultural syllabus., 2018)
"'A Dostoevsky Companion: Texts and Contexts' aims to help students and readers navigate the writer's fiction and his world, to better understand the cultural and sociopolitical milieu in which Dostoevsky lived and wrote. Rather than offer a single definitive view of the author, the book contains a collection of documents from Dostoevsky's own time (excerpts from his letters, his journalism, and what his contemporaries wrote about him), as well as extracts from the major critical studies of Dostoevsky from the contemporary academy. The volume equips readers with a deeper understanding of Dostoevsky's world and his writing, offering new paths and directions for interpreting his writing"--Publisher's info